The Relation Between Multinationality and Tax Haven on Transfer Pricing: Moderated by Institutional Ownership (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the influence of multinationality and tax haven utilization on transfer pricing activities, with institutional ownership as a moderating variable. The research focuses on energy sector companies in Indonesia, using 70 data samples obtained from company reports and financial statements. Regression analysis with moderation was employed to test the hypotheses. The findings reveal that both multinationality and tax haven practices significantly influence transfer pricing activities. However, institutional ownership does not moderate the relationship between multinationality and transfer pricing but does moderate the relationship between tax haven and transfer pricing. These findings indicate that multinational expansion and the use of tax havens play an essential role in determining corporate transfer pricing behavior. Furthermore, the presence of institutional ownership strengthens the influence of tax haven utilization on transfer pricing practices, showing that ownership structure affects how companies manage their tax-related strategies. This research contributes to a better understanding of the determinants of transfer pricing in multinational enterprises and offers practical implications for policymakers in designing effective tax regulations and governance standards related to corporate taxation.